Crystal structure of the essential transcription antiterminator M2-1 protein of human respiratory syncytial virus and implications of its phosphorylation - Tanner, S; Ariza, A; Richard, C; al., E (National Academy of Sciences, 2014)
The M2-1 protein of the important pathogen human respiratory syncytial virus is a zinc-binding transcription antiterminator that is essential for viral gene expression. We present the crystal structure of full-length M2-1 protein in its native tetrameric form at a resolution of 2.5 Å. The structure reveals that M2-1 forms a disk-like assembly with tetramerization driven by a long helix forming a four-helix bundle at its center, further stabilized by contact between the zinc-binding domain and adjacent protomers. The tetramerization helix is linked to a core domain responsible for RNA binding activity by a flexible region on which lie two functionally critical serine residues that are phosphorylated during infection. The crystal structure of a phosphomimetic M2-1 variant revealed altered charge density surrounding this flexible region although its position was unaffected. Structure-guided mutagenesis identified residues that contributed to RNA binding and antitermination activity, revealing a strong correlation between these two activities, and further defining the role of phosphorylation in M2-1 antitermination activity. The data we present here identify surfaces critical for M2-1 function that may be targeted by antiviral compounds.